2012
DOI: 10.2174/1876524601205010008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Alloxan-Induced Diabetic Rats with Metformin or Glitazones is Associated with Amelioration of Hyperglycaemia and Neuroprotection

Abstract: Neurobehavioural and cognitive impairments are reportedly associated with both types of diabetes mellitus; and the structural and molecular aberrations in support of these are emerging. In the present study, we report the effects of induced diabetes and its treatment with or without oral hypoglycaemic drugs on the morphology and oxidative stress status of the prefrontal cortex. Hyperglycaemia was induced in fasted Wistar rats with alloxan (150 mg/kg body weight). Hyperglycaemic rats were treated with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Magnesium supplementation in this study, either alone or in combination with metformin, exerted a hypoglycemic effect, as did metformin in diabetic treated animals, which for magnesium may be ascribed to its documented potentiation of insulin secretory activities, its glucose regulatory and blood glucose stabilizing effects [7, 22]. Similarly the effects of Metformin, the most frequently prescribed first line therapy for individuals with type 2 diabetes [23], seen in this study may be linked to its ability to increase insulin mediated glucose utilization in peripheral tissues (such as muscle and liver) and thus improve glycemic control [24].…”
Section: Discussionmentioning
confidence: 90%
“…Magnesium supplementation in this study, either alone or in combination with metformin, exerted a hypoglycemic effect, as did metformin in diabetic treated animals, which for magnesium may be ascribed to its documented potentiation of insulin secretory activities, its glucose regulatory and blood glucose stabilizing effects [7, 22]. Similarly the effects of Metformin, the most frequently prescribed first line therapy for individuals with type 2 diabetes [23], seen in this study may be linked to its ability to increase insulin mediated glucose utilization in peripheral tissues (such as muscle and liver) and thus improve glycemic control [24].…”
Section: Discussionmentioning
confidence: 90%
“…Treatment with different substances containing antioxidants prevented the harmful effects of diabetes mellitus on neurological tissues. In the previous studies [38][39][40] , it has been found that metformin prevents the brain damage by reducing oxidative stress. The results of our study are in line with these studies, and significant prevention of the neuronal tissue damage was found in all areas of the brain of the animals.…”
Section: Discussionmentioning
confidence: 97%
“…During this period, animals in all groups had free access to standard diet and water. The blood was withdrawn by retroorbital plexus method [ 22 ]. On the same day, the blood glucose levels were estimated by using glucometer (Johnson & Johnson Pvt.…”
Section: Experimental Methodsmentioning
confidence: 99%